Critical Care in the Era of Global Economic Crisis: a Nursing Ethics Perspective - Papathanassoglou, Elizabeth; Mpouzika, Meropi (My University, 2012)
In the midst of a devastating global economic crisis it becomes increasingly evident that it is the crisis of values that we have to restore first. In healthcare, justice, non-maleficence, beneficence and autonomy are core thical principles reflecting universal ideals that advocate for people’s rights to life, health, protection and decency. While in nursing and the healthcare sciences we take honor in protecting these rights, and nation states strive to provide equal access to health for all, in the arena of finances, we came to accept and tolerate a different set of values. It appears to be assumed that market forces and the enterprise economic system, leading banks not excluded, can be let free to pursuemaximal profits, even at the expense of social state provisions, such as health. Although the impact of the recent economic crisis on individual countries may vary greatly depending on the economic capacity of each country, the majority of European countries report budget cuts in the health sector, concerns about quality of care and patient safety and in some instances downgrading of nursing (EFN, 2012). It appears as if Europeans may pay for the economic crisis with their health(Suhrcke and Stuckler, 2012) Herein, we will delineate the impact of the economic crisis on health care, and particularly on its most highly specialized/high-technology domains, such as critical care, with a focus on European countries. Moreover, we will argue that extensive moral reflection and action are needed in order to respond effectively to the crisis without compromising essential structures within individual countries, such as education and healthcare. To highlight specific points, we will draw examples from the current Greek situation. Compared to other European countries, Greece has been probably affected first and the most by the financial recession. Moreover, since Greece has been put under surveillance by the International Monetary Fund (IMF), the country’s health sector has suffered various forms of restraints, including an overall restriction of health costs, majorsalary deductions, and reductions in drug spending, utilities and public health services (IMF, 2010), which have had unfavorable effects on health outcomes (Karidis et al., 2011; Kentikelenis et al., 2011). Although regrettably, at the present point, Greece may be a window into an ostensible future that other European countries have to avoid
Keywords: Nursing; Nursing ethics; Economic crisis; Medical care; Greece